Comparison between Effects of Fentanyl and Dexmedetomidine as Sedative in Elective Caesarean Section Under Subarachnoid Anaesthesia - Karim, Md Enayet; Rashid, RAM Mostafijur; Akram, Mohammad Saleh; Ershad, Reza (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2023)
Background: Regional anaesthesia has become an important anaesthetic technique now a days. The use of spinal (Subarachnoid) anaesthesia is often limited by the unwillingness of patients to remain awake during surgery. Pharmacologically induced tranquility improves acceptance of regional technique. This study compares Fentanyl and Dexmedetomidine in terms of onset and recovery of sedation, haemodynamic effects, respiratory effects and adverse effects of both the drugs during elective Caesarian section under spinal anaesthesia. Materials and methods: This randomized clinical trial included 60 ASA (American Society of Anaesthesiologists) grade I patients between age 20-40 years undergoing elective caesarean sections under subarachnoid anaesthesia during the period January 2022 to June 2022.Patients were randomly allocated to one of two groups: Fentanyl group (Group F, n=30), who received Fentanyl in a single dose of 0.5mcg/kg and Dexmedetomidine group (Group D, n=30), who received Dexmedetomidine in a single dose of 2mcg/kg. Spinal anaesthesia was conducted by injecting a hyperbaric solution of 0.5% bupivacaine 3ml through a 25G spinal needle at L3-4 level. All parameters were documented at 5 min intervals until arousal of the patient. The onset of sedation i.e. time from iv (Intravenous) injection of Fentanyl or Dexmedetomidine to closure of eye lids (OAA/S score of 3) and the arousal time from sedation i.e. time from closing of the eye lids to OAA/S score of 5 (Patient is awake clinically) were noted. Any complication during operation was documented. The patient’s satisfaction with the sedation was assessed by the 5 point ‘Likert verbal rating scale.’ Results: There was no significant difference of mean blood pressure and mean heart rate between the two groups in different time intervals (p>0.05). Time of onset of sedation was comparable between Fentanyl and Dexmedetomidine (p value 0.210). The arousal time i.e. duration of sedation was significantly longer with Dexmedetomidine than Fentanyl (p<0.05). Fentanyl was associated with significantly higher incidence of some adverse effects like nausea, vomiting than Dexmedetomidine (46.66% vs 13.33%, p<0.05). Significant percentage of patients was satisfied with Dexmedetomidine than Fentanyl (86.66% vs 20%,p<0.001). Conclusion: The study showed that the arousal time i.e. duration of sedation was significantly longer with Dexmedetomidine which is beneficial for the patient in single dose technique for sedation. Moreover, Fentanyl was associated with high incidence of some adverse effects like nausea, vomiting. Thus it is recommended that Dexmedetomidine is a better choice than Fentanyl for sedation in single dose technique during subarachnoid block for caesarean section. Chatt Maa Shi Hosp Med Coll J; Vol.22 (1); January 2023; Page 48-52